1995
DOI: 10.1164/ajrccm.151.1.7812557
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of sinus arrest and atrioventricular conduction block in patients with sleep apnea during nasal continuous positive airway pressure.

Abstract: Sinus arrest and atrioventricular (AV) block have been demonstrated in as much as 30% of patients with sleep apnea (SA). The reversal of heart block after tracheostomy has been shown. Nasal continuous positive airway pressure (nCPAP) now is widely used as the treatment of SA, but little data are available on the effect of nCPAP on heart block in patients with SA. During a 17-mo period 239 patients were found to have SA in an ambulatory study. Heart block was identified in 17 (16 male, one female) of these pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
20

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(110 citation statements)
references
References 0 publications
3
86
1
20
Order By: Relevance
“…226,235 Electrophysiological characteristics of the sinus node and atrial conduction system in OSA subjects with nocturnal bradyarrhythmias were normal or nearly normal while awake, and CPAP reversed the bradyarrhythmias, suggesting that OSA may have induced the arrhythmias. 234,236,237 First-line treatment of bradyarrhythmias in the setting of obstructive apneas and normal conduction would consist of treatment of OSA. Data emerging from the European Multi-Center Polysomnographic Study show a remarkably high prevalence (59%) of sleep apnea syndrome in patients with pacemakers.…”
Section: Prevalence Of Arrhythmias In Sleep Apneamentioning
confidence: 99%
“…226,235 Electrophysiological characteristics of the sinus node and atrial conduction system in OSA subjects with nocturnal bradyarrhythmias were normal or nearly normal while awake, and CPAP reversed the bradyarrhythmias, suggesting that OSA may have induced the arrhythmias. 234,236,237 First-line treatment of bradyarrhythmias in the setting of obstructive apneas and normal conduction would consist of treatment of OSA. Data emerging from the European Multi-Center Polysomnographic Study show a remarkably high prevalence (59%) of sleep apnea syndrome in patients with pacemakers.…”
Section: Prevalence Of Arrhythmias In Sleep Apneamentioning
confidence: 99%
“…2 A few studies have reported the reversal of heart block after tracheostomy or nasal continuous positive airway pressure. However, these were not bradydysrhythmias induced by apnea but SDB induced by chronic bradydysrhythmia such as third-degree AVB or SND.…”
Section: Discussionmentioning
confidence: 99%
“…This may result in severe nocturnal bradyarrhythmia. In the study of 239 OSA patients by Becker et al (1995), bradyarrhythmia occurred only during apnea and hypopnea. In some studies, these bradyarrhythmias occurred more frequently during REM sleep accompanied by at least a 4% decrease in oxygen saturation (Becker et al, 1995;Koehler et al, 1998;Koehler et al, 2000).…”
Section: Bradyarrhythmiasmentioning
confidence: 97%
“…In the study of 239 OSA patients by Becker et al (1995), bradyarrhythmia occurred only during apnea and hypopnea. In some studies, these bradyarrhythmias occurred more frequently during REM sleep accompanied by at least a 4% decrease in oxygen saturation (Becker et al, 1995;Koehler et al, 1998;Koehler et al, 2000). Conversely, in the study by Guilleminault et al (1983), in 3 patients extreme sinus bradycardia occurred during nonREM sleep, and sinus arrest was associated with apneas during REM sleep.…”
Section: Bradyarrhythmiasmentioning
confidence: 97%
See 1 more Smart Citation